THE USE OF SIGHT FOR THE STATIC BALANCE MAINTENANCE IN YOUNG PEOPLE (Fiep Bulletin - online, 2014)
This study was aimed to verify the amplitude of displacement and the antero-posterior as well as the medium-lateral displacement of the force center of 34 subjects of both sexes with average age around 20, 33 ± 1,86 years old during the static balance. It was used two platforms of force, which worked in 100Hz, distant 5,5 mm one from each other.  The open-eye and the closed-eye situations were analyzed in two conditions: firstly with the members over one platform; then, with the members over two platforms.  The conclusion is that when the visual information was taken out, the individuals presented meaningful differences for both the amplitude of displacement and the force center medium displacement in the conditions analyzed, especially in the anterior-posterior direction.
Keywords: static balance; visual information